Performance audit of the regulatory system of Coca Leaf S.A. (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2026)
The Peruvian public company responsible for the legal commercialization of coca leaf reported profits for over 60 years. However, between 2016 and 2023, it accumulated losses of approximately twenty million. The objective of this study is to analyze the alignment of performance auditing with the institutional strategic plan of its branch located in San Sebastián, Cusco. The research is basic in nature, with a qualitative approach, and employs triangulation as a technique to generate new insights, including interviews, official reports, and regulatory analysis. The results reveal a consensus among interviewees regarding the entity’s limitations in achieving its strategic objectives, attributed to the low supply of quality products, the expansion of the illegal market, and regulatory ambiguity. Weaknesses were identified in procurement processes, commercial control, and institutional management, exacerbated by high turnover among executive personnel. The performance audit suggests reorienting the strategy toward results-based management, strengthening inter-institutional oversight, promoting quality policies, and reviewing the international regulatory framework. It is concluded that the institutional strategic plan is neither adequately updated nor aligned with internal realities or foreign policy objectives, resulting in normative gaps and contradictions. This situation has facilitated the growth of the illegal market, which currently dominates more than 90% of the sector, highlighting the urgent need to redesign the entity’s commercial and regulatory approach.
Keywords: Performance Audit; Public Policies; Results-Based Management; Regulatory System; Coca Leaf